The Rise and the Fall of Indonesia’s Climate Diplomacy: Case Study of the Joint Crediting Mechanism in Indonesia - Verdinand Robertua; Seni Rohani Sihura (Jurnal Hubungan Internasional, 2020)
Climate change is an urgent problem. Many countries have collaborated in mitigating the impact of climate change, including Indonesia and Japan. Both countries agreed on a scheme for cooperation in a low-carbon project, namely the Joint Crediting Mechanism (JCM). The implementation of JCM in Indonesia is new hope for Indonesia’s climate diplomacy in promoting clean and renewable energy. This research aims to review the application of JCM in Indonesia using the case study of the Jakabaring Solar Power Plant in Palembang. This research collected primary data through the interview with related officials, local companies, and civil society. This research showed that the Indonesian government did not consistently support clean energy development. Carbon-intensive industry players still played a dominant role in Indonesia’s climate diplomacy.